Fragile X Syndrome Secondary to in Vitro Fertilization with a Family Egg Donor, A Case Report and Review of the Literature - Laura Yuriko González- Teshima; César Payán-Gómez; Wilmar Saldarriaga (Tehran University of Medical Sciences, 2021)
Objective: To evidence the need for screening fragile X syndrome (FXS) in egg donors in assisted reproduction protocols. Case report: This is the report of a boy with FXS who inherited the mutated allele from an ovule donated by the mother´s sister through an assisted reproduction protocol. Identifying premutation (PM) carriers of FXS amongst gamete donors isn't part of the obligatory genetic analysis for donors and is only considered by most of the in vitro fertility societies and guidelines as part of the extension screening tests. Conclusion: It is cost-effective to do pre-conceptional screening for the PM or full mutation (FM) of the FMR1 gene affected in FXS in every woman undergoing assisted reproductive methods, including gamete donors even without a positive family history of intellectual disabilities. This case supports the need of rethinking the guidelines on the necessary gamete donor screening tests in assisted reproduction protocols.